Beyond genetics. Influence of dietary factors and gut microbiota on type 1 diabetes. Issue 22 (18th April 2014) - Nielsen, Dennis S.; Krych, Łukasz; Buschard, Karsten; Hansen, Camilla H.F.; Hansen, Axel K.
Abstract : Type 1 diabetes (T1D) is an autoimmune disease ultimately leading to destruction of insulin secreting β‐cells in the pancreas. Genetic susceptibility plays an important role in T1D etiology, but even mono‐zygotic twins only have a concordance rate of around 50%, underlining that other factors than purely genetic are involved in disease development. Here we review the influence of dietary and environmental factors on T1D development in humans as well as animal models. Even though data are still inconclusive, there are strong indications that gut microbiota dysbiosis plays an important role in T1D development and evidence from animal models suggests that gut microbiota manipulation might prove valuable in future prevention of T1D in genetically susceptible individuals.